The Influence of Financial Behavior, Income, and Risk on the Use of Shopee PayLater among the People of Singkawang City with Locus of Control as a Moderating Variable - Elfi Hiddaryah; Edy Suryadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of financial behavior, income, and risk on the use of Shopee PayLater services in Singkawang City, with locus of control serving as a moderating variable. The research employs an associative quantitative approach. A total of 150 active Shopee PayLater users were selected as respondents using purposive sampling. The research instruments were tested for validity and reliability, followed by data analysis through multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that financial behavior and income have a significant positive effect on the use of Shopee PayLater, while risk does not show a significant influence. Locus of control is proven to moderate the relationship between financial behavior and income with the use of Shopee PayLater, but it does not moderate the relationship between risk and the use of the service. These findings suggest that individuals with a high level of self-control tend to use digital credit services more wisely. This study offers a meaningful contribution to understanding the psychological and financial factors that influence consumer behavior in using digital financial services in the era of financial technology.